Unintended indirect effects limit elk productivity from supplemental feeding in the Greater Yellowstone Ecosystem - Brian S. Dugovich; Emma M. Tomaszewski; Eric K. Cole; Sarah R. Dewey; Daniel R. MacNulty; Brandon M. Scurlock; Daniel R. Stahler; Paul C. Cross (Ecosphere)
Abstract The widespread practice of supplemental feeding, a bottom‐up forcing of resource availability, is intended to improve wildlife population health and survival. However, supplemental feeding could trigger indirect effects by altering predation rates and disease dynamics. We investigated the effects of feeding on three key elk (Cervus canadensis) population productivity metrics (calf:cow ratios, annual change in elk density, and harvestable surplus) across 13 regions in the Greater Yellowstone Ecosystem (GYE) over 26 years. Incorporating previous population size, climate, predator, and harvest data in a Bayesian regression framework revealed new insights about elk productivity metrics in the GYE. Supplemental feeding was associated with increased calf:cow ratios (4.9%) but was not substantially related to changes in elk density and harvestable surplus, which are both management targets. Notably, the feeding effect on calf:cow ratios appeared to be offset by increased wolf (Canis lupus) and grizzly bear (Ursus arctos horribilis) predation. We hypothesize that increased elk productivity resulting from supplemental feeding is primarily transferred to predator and pathogen trophic levels in this system with limited observed effects on elk abundance and harvestable surplus. Anthropogenic food resources may have unintended indirect consequences on other trophic levels that potentially limit the direct impacts of feeding.